The severity of depressive symptoms as a mediator in the sleep-osteoarthritis risk pathway: insights from the ELSA cohort - Wang, Junbo; Duan, Lincheng; Duan, Xin; Chen, Li; Chen, Zhichao (Frontiers in Nutrition, 2025)
BackgroundOsteoarthritis (OA) is a major cause of disability in middle-aged and older adults, yet its risk factors and mechanisms require further investigation. The connection between sleep disturbances and OA risk remains controversial, with underlying mechanisms unclear. The research aimed to examine the prospective association between sleep quality, sleep duration, and incident OA, and to evaluate whether the severity of depressive symptoms partially mediate this association.MethodsThis analysis included 4,147 ELSA participants aged ≥50 years without baseline OA. Sleep quality (good/intermediate/poor) and duration (short: <7 h, optimal: 7-8 h, long: >8 h) were assessed via questionnaires. The severity of depressive symptoms was measured using the CES-D scale. Incident OA was determined by self-reported physician diagnosis. Multivariable Cox regression modeled associations between sleep (quality/duration) and OA risk. Threshold analysis and restricted cubic splines (RCS) explored the dose–response relationship for sleep duration. Mediation analysis quantified the severity of depressive symptoms’ role in the sleep-OA connection.ResultsDuring 102 months of follow-up, 1,333 new OA cases were reported. Cox regression showed that intermediate and poor sleep quality significantly increased OA risk (HR = 1.23 and 1.74, respectively). RCS analysis revealed a U-shaped curve, with the lowest OA risk at 8 h of sleep. Short sleep (<7 h) was associated with higher OA risk (HR = 1.21), while long sleep (>8 h) showed no significant association. The severity of depressive symptoms mediated the relationship between both sleep quality and sleep duration with OA risk (mediation proportions: 22.39 and 22.11%, respectively). Sensitivity analyses confirmed result robustness.ConclusionPoor sleep quality and short sleep duration are independent risk factors for incident OA in middle-aged and older adults. The severity of depressive symptoms partially mediates this relationship. Maintaining optimal sleep duration (8 h), improving sleep quality, and addressing depressive symptoms may help reduce OA risk.